The Pattern of Intraocular Pressure After Phacoemulsification Surgery In Senile Cataract - Nur Shani Meida; Ahmad Ikliluddin; Yunani Setyandriana; Vania Rahmawati (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2023)
Phacoemulsification is a surgical procedure for cataracts, which can increase intraocular pressure (IOP) and cause blindness due to glaucoma. It was known that the pattern of IOP changes after phacoemulsification surgery in senile cataracts. This study was an observational analytic study without a control group design. The study population was male and female senile cataract patients over 40 years of age who underwent phacoemulsification surgery at Kebumen Eye Centre Clinic in 2020. Intraocular pressure measurements using a Noncontact Tonometry by a nurse were carried out before surgery (D-0) and postoperatively on day 2 (D-2), day 9 (D-9), day 16 (D-16), and day- 23 (D-23). The data were analyzed using the Friedman test followed by the Post Hoc LSD test. The Friedman test results showed significant differences (p 0.05) in the IOP measurement at D-0, D-2, D-9, D-16, and D-23. Wilcoxon post hoc test showed IOP measurements on D-2  increased and then decreased normally. There was a change in the IOP pattern after phacoemulsification surgery, in which the IOP increased significantly on D-2 and then decreased normally.